Industry present situation,existing problems and strategy suggestion of blockchain - Haitao MEI; IUJie L (Dianxin kexue)
Blockchain is one kind of collective and decentralized database technology without trust among the nodes.In essence,it is a distributed database which has no delete and update operations.The technical principles of blockchain was introduced,its industry situations and existing problems were discussed,and related policy suggestions were proposed from government,industry association and academic institution.